Tinjauan Terhadap Praktik Bimbingan Pranikah Dan Realitas Perceraian Di Kecamatan Bangsri - Ratnasari, Kiki Novita (Isti`dal : Jurnal Studi Hukum Islam, 2024)
Pre-marital guidance is guidance provided by the Office of Religious Affairs to prospective brides and grooms who are about to get married. Pre-marital guidance aims to provide knowledge and understanding in domestic life as well as providing provisions for building a sakinah, mawaddah, warahmah household. This research aims to determine the factors that cause divorce in Bangsri District and the quality of the role of the Bangsri District Religious Affairs Office in the practice of pre-marital guidance and the reality of divorce in Bangsri District. In this research, the type of research used is field research. The research method used is a qualitative method with a statutory approach. The research results show that the factors causing divorce in Bangsri sub-district are economic factors, constant disputes and quarrels, leaving one of the parties, the presence of a third party, and domestic violence. Then the quality of the role of the Bangsri District Religious Affairs Office (KUA) in implementing pre-marital guidance is not yet optimal to reduce the divorce rate, because its implementation is still not fully in accordance with regulations.